An Electrochemical Impedance Spectroscopy Study on the Effects of the Surface- and Solution-Based Mechanisms in Li-O2 Cells. Issue 9 (1st January 2016) - Knudsen, Kristian B.; Vegge, Tejs; McCloskey, Bryan D.; Hjelm, Johan
Abstract : The maximum discharge capacity in non-aqueous Li-O2 batteries has been limited to a fraction of its theoretical value, largely due to a conformal deposition of Li2 O2 on the cathode surface. However, it has recently been established that additives that increase the shielding of either O2 − or Li + will activate the formation of toroidal shaped Li2 O2, thereby dramatically increasing cell capacity. Here we apply porous electrode theory to electrochemical impedance measured at the Li-O2 cathode to investigate changes in the surface- and ionic resistance within the pores under conditions where either the surface-mechanism or the solution-mechanism is favored. Our experimental observations show that (i) an additional charge transfer process is observed in the impedance spectrum where the solution-based mechanism is favored; (ii) that the changes in the ionic resistance in the cathode during discharge (related to Li2 O2 build up) is much greater in cells where the solution-based mechanism is activated and can qualitatively determine the extent of discharge product deposited within the pores of the cathode versus the deposition extent at the electrode/electrolyte interface; and (iii) that the observed "sudden-death" during discharge is a consequence of the increasing charge transfer resistance regardless of whether Li2 O2 forms predominantly through either the surface- or solution-based mechanism.